Why Should Nodule Cysteine-Rich (NCR) Peptides Be Absent From Nodules of Some Groups of Legumes but Essential for Symbiotic N-Fixation in Others? - Downie, J. Allan; Kondorosi, Eva (Frontiers in Agronomy, 2021)
In nitrogen-fixing nodules of legumes such as pea (Pisum) and Medicago spp. the plant induces terminal differentiation in the rhizobial endosymbionts by targeting nodule-specific cysteine-rich defensin-like peptides into the bacteria. However, in nodules of other legumes such as soybean and Lotus spp. terminal bacterial differentiation does not occur; these legumes lack genes encoding equivalent peptides controlling rhizobial development. Here we review the effects of some of these peptides on rhizobia and address the question as to how and why such peptides may have evolved to enslave rhizobia and become essential for nitrogen fixation in some clades of legumes but not in others.